2023
DOI: 10.1021/acsomega.2c06555
|View full text |Cite
|
Sign up to set email alerts
|

Arabic Gum-Grafted-Hydrolyzed Polyacrylonitrile@ZnFe2O4 as a Magnetic Adsorbent for Remediation of Levofloxacin Antibiotic from Aqueous Solutions

Abstract: The Arabic gum-grafted-hydrolyzed polyacrylonitrile/ZnFe 2 O 4 (AG-g-HPAN@ZnFe 2 O 4 ) as organic/inorganic adsorbent was obtained in three steps using grafted PAN onto Arabic gum in the presence of ZnFe 2 O 4 magnetic nanoparticles and then hydrolysis by alkaline solution. Fourier transform infrared (FT-IR), energy-dispersive X-ray analysis (EDX), field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), thermogravimetric analysis (TGA), vibrating sample magnetometer (VSM), and the Brunaue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…7,8 Nowadays, the compilation of Watson-Crick pairing methods and nucleotide synthesis strategies has opened new windows for researchers in the field of materials science. 9,10 Generally, hydrogels are considered as a highly appropriate substrate in various areas such as energy, [11][12][13] catalysis, [14][15][16][17][18][19] environmental sciences, [20][21][22][23][24][25][26] and medical applications. [27][28][29][30][31] Specifically, in the area of drug delivery to cancer tissues, hydrogels are widely used because they are capable of absorbing water molecules and swelling in the target organ, resulting in drug release in a controlled manner.…”
Section: Iman Zarementioning
confidence: 99%
“…7,8 Nowadays, the compilation of Watson-Crick pairing methods and nucleotide synthesis strategies has opened new windows for researchers in the field of materials science. 9,10 Generally, hydrogels are considered as a highly appropriate substrate in various areas such as energy, [11][12][13] catalysis, [14][15][16][17][18][19] environmental sciences, [20][21][22][23][24][25][26] and medical applications. [27][28][29][30][31] Specifically, in the area of drug delivery to cancer tissues, hydrogels are widely used because they are capable of absorbing water molecules and swelling in the target organ, resulting in drug release in a controlled manner.…”
Section: Iman Zarementioning
confidence: 99%
“…For instance, forming a concentrated sludge is a time and energy consuming process with low efficacy and expensive operation. Therefore, among all of the processes for contaminant removal from water, adsorption is suggested due to its economical and practicable procedure, enhanced efficacy, selectivity and retrievability, and affordability 12 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Ternes et al [ 16 ] reported that conventional methods, including oxidation, flocculation and coagulation, ion exchange, phytoremediation and sedimentation, are ineffective in eliminating the abovementioned substances from wastewater. On the other hand, the non-conventional method of adsorption is more effective and efficient [ [17] , [18] , [19] , [20] , [21] ]. The presence of benzene rings and functional groups on the structures of IBU and MB enhances the ability of carbonaceous material derived from agricultural waste to adsorb these substances from water [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%